2007
DOI: 10.1177/10634266070150040201
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Dynamics of Aggression and the Prevention of School Violence

Abstract: The authors consider school violence from a dynamic systems conceptualization of aggression. This perspective suggests that aggression and school violence involve the contributions of both school social dynamics and the developmental histories of youth who are at risk for involvement in antisocial behavior. The authors present the concept of correlated constraints to describe the systematic alignment of developmental factors and their role in behavioral continuity and realignment. Building from this perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 54 publications
(52 reference statements)
0
50
0
5
Order By: Relevance
“…On this point, Farmer and colleagues (Farmer, Farmer, Estell, & Hutchins, 2007) build on a prevention framework outlined by the Institute of Medicine (Mrazek & Haggerty, 1994) and the more recent but parallel Response-to-Intervention framework (c.f. Burns & Coolong-Chaffin, 2006) that specifies three levels of assessments/interventions: universal for all children, targeted for students at risk, and indicated for individuals already experiencing problem behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…On this point, Farmer and colleagues (Farmer, Farmer, Estell, & Hutchins, 2007) build on a prevention framework outlined by the Institute of Medicine (Mrazek & Haggerty, 1994) and the more recent but parallel Response-to-Intervention framework (c.f. Burns & Coolong-Chaffin, 2006) that specifies three levels of assessments/interventions: universal for all children, targeted for students at risk, and indicated for individuals already experiencing problem behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Some have concluded that social and academic factors come together to create a "developmentally hazardous" environment for positive adjustment (Felner et al, 2007, p. 211; see also Juvonen, 2007). Drawing from stage-environment and other ecological perspectives, scholars have argued that the target of intervention must be schools-to make them more developmentally sensitive places that support positive adjustment in social, behavioral, and academic realms (Farmer, 2000;Farmer, Farmer, Estell, & Hutchins, 2007;Felner et al, 2006;. The primary focus of interventions has been middle schools, and in particular, the middle school transition year.…”
Section: Effects Of a Developmentally Based Intervention With Teachermentioning
confidence: 97%
“…As ethnographic descriptions of bullying and victimization suggest, such youth may become social scapegoats for others who are trying to reduce their own social vulnerability (Adler & Adler, 1998;Evans & Eder, 1993). Therefore, interventions to support highly disliked youth should consider how peer-group dynamics and general ecological factors contribute to their negative social reputations while simultaneously addressing their individual social competence problems (Farmer, Farmer, Estell, & Hutchins, 2007;Swearer & Doll, 2001).…”
Section: Discussionmentioning
confidence: 99%